On the numerical-analytic investigation of parametrized problems with nonlinear boundary conditions - Rontó, M.; Shchobak, N.M. (Нелінійні коливання, 2003)
We consider a parametrized boundary-value problem containing an unknown parameter both in the nonlinear ordinary differential equations and in the nonlinear boundary conditions. By using a suitable change of variables, we reduce the original problem to a family of those with linear boundary conditions plus some nonlinear algebraic determining equations. We construct a numerical-analytic scheme suitable for studying the solutions of the transformed boundary-value problem.